The CoREST complex regulates multiple histone modifications temporal-specifically in clock neurons. - Lv, P.; Zhao, Z.; Hirano, Y.; Du, J. (Open biology, 2024)
Epigenetic regulation is important for circadian rhythm. In previous studies, multiple histone modifications were found at the Period (Per) locus. However, most of these studies were not conducted in clock neurons. In our screen, we found that a CoREST mutation resulted in defects in circadian rhythm by affecting Per transcription. Based on previous studies, we hypothesized that CoREST regulates circadian rhythm by regulating multiple histone modifiers at the Per locus. Genetic and physical interaction experiments supported these regulatory relationships. Moreover, through tissue-specific chromatin immunoprecipitation assays in clock neurons, we found that the CoREST mutation led to time-dependent changes in corresponding histone modifications at the Per locus. Finally, we proposed a model indicating the role of the CoREST complex in the regulation of circadian rhythm. This study revealed the dynamic changes of histone modifications at the Per locus specifically in clock neurons. Importantly, it provides insights into the role of epigenetic factors in the regulation of dynamic gene expression changes in circadian rhythm.